Exploration of the Traditional Culinary Heritage of the Balik Tribe: Contributions to Tourism in the Capital of the Archipelago - Ninawati Syahrul; Sastri Sunarti; Janeke Peggy Slippy; Atisah Atisah; Agus Iswanto; Harits Fadlly (Jurnal IKADBUDI, 2025)
Abstract Balik's traditional cuisine has high historical and social value, yet is poorly known outside the local community. This challenge is compounded by modernization and lifestyle changes that threaten the survival of these culinary traditions. The lack of documentation and research on the recipes, cooking techniques and cultural values of Balik cuisine further exacerbates the situation, making this great potential untapped in tourism development in the nation's capital. Therefore, an in-depth exploration is needed to understand and promote the traditional Balik cuisine as an integral part of the tourism strategy in the nation's capital. This research aims to explore the culinary of Suku Balik and its contribution to tourism development in the nation's capital. This research uses a qualitative approach with ethnographic methods, which involves participatory observation, in-depth interviews, and literature analysis. Previous literature shows that traditional cuisine plays an important role in promoting cultural identity and attracting tourists, but there have not been many studies that specifically focus on the Balik Tribe's cuisine in the context of the development of the National Capital. This research differs by emphasizing the specific context of the National Capital City and a holistic approach to culture and tourism. The results show that Suku Balik cuisine has great potential to be developed as a culinary tourism attraction in the National Capital, with its rich flavors, unique local ingredients, and interesting cultural stories. However, there are challenges in terms of preserving traditional recipes, preparing human resources, and marketing. Recommendations from this study are as follows. (1) Training and education for local communities to maintain and develop traditional culinary skills. (2) Collaboration between the government, tourism actors, and local communities to create attractive culinary tour packages. (3) Marketing strategies that emphasize the uniqueness of the Balik Tribe's culinary. Suggestions for future research are to conduct a more in-depth study of the economic impact of traditional culinary tourism development and further explore the potential for collaboration between regions to promote the culinary archipelago. Keywords: Traditional culinary, Balik Tribe, Capital City of the Archipelago